Soviet, but not Russian – Petro Shelest’s Vision of Ukraine - Studenna-Skrukwa, Marta (Sensus Historiae, 2022)
The article “Soviet, but not Russian – Petro Shelest’s vision of Ukraine” was devoted to the figure of First Secretary of the Central Committee of the Communist Party of Ukraine from 1963 to 1972 and to the critical analysis of his publication legacy. The article assumes that the rule of any republican Soviet leader can be characterised by comparing him with other leaders of his time. A positive point of reference could be the attitude of Johannes Käbin, the First Secretary of the Communist Party of Estonia from 1950–1978 and the Chairman of the Supreme Council of the Estonian Soviet Socialist Republic, who followed a long-standing policy of manoeuvring between submission to Moscow and looking after the interests of Tallin. A negative example, in turn, is the way in which Lazar Kaganovich (1925–1928, 1947) and Stanislav Kosior (1928–1934), First Secretaries of the Communist Party of Ukraine (Bolsheviks), administered the country. They put into practice a criminal Stalinist policy of constructing a totalitarian regime with total disregard for the welfare of the republic they governed. A fundamental question, around which the content of this article focuses, concerns the place Petro Shelest would take on the axis of attitudes and the place occupied by Ukraine in the vision of the Soviet state signed with his name.